EFT study of critical properties of the mixed spin-2 and spin- 3/2 Blume Capel model on the honeycomb lattice - YESSOUFOU, RACHIDI ADENIYI AKAMBI (My University, 2018)
We use theoretical and numerical calculations in the framework of the effective-field theory to examine the rigorous effects of the crystal field interactions of the mixed spin-2 and spin- 32 Blume–Capel model on the honeycomb lattice in the presence of an external magnetic field. The ground state phase diagram has been constructed. Thermal changes of the order parameters and other thermodynamic quantities of interest and their influence on the phase diagrams of the model have been thoroughly investigated. The system shows very interesting critical properties including continuous and discontinuous phase transitions, tricritical points and compensation temperatures which are revealed in specific ranges of the parameters space. Our numerical findings are compared to those obtained by other methods and reliable agreements are recovered.
Keywords: Critical phenomena; thermal changes; crystal fields interactions; mixed spin-2; and spin- 3/2 .